2016
DOI: 10.1186/s13046-016-0334-y
|View full text |Cite
|
Sign up to set email alerts
|

Sustained delivery of siRNA/PEI complex from in situ forming hydrogels potently inhibits the proliferation of gastric cancer

Abstract: BackgroundGastric cancer remains a major cause of mortality and morbidity worldwide. In recent years, gene-based therapeutic strategies were confirmed promising in cancer inhibition and attracted great attention. RNA interference (RNAi) is a powerful tool for gene therapy and has been widely employed to aid in treatment for various diseases, especially cancers. However, effective delivery of small interfering RNA (siRNA) to target cells in vivo remains a challenge for that it is prone to degradation and only l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Krebs et al [399] showed the collagen chains ability to locally load siRNA (small interfering RNA) and then release it in a controlled manner in order to extend the effect directly at the specific target. Peng et al [400] tested collagen based hybrid hydrogels for the Id1-siRNA targeting and its delivery and sustained release for the treatment of gastric cancer. To improve the siRNA delivery by stimulating the target of Id1-siRNA into the defect cells and prolonging the silencing effect, cationic PEI was further engaged for scaffold modification.…”
Section: Drug and Molecule Deliverymentioning
confidence: 99%
“…Krebs et al [399] showed the collagen chains ability to locally load siRNA (small interfering RNA) and then release it in a controlled manner in order to extend the effect directly at the specific target. Peng et al [400] tested collagen based hybrid hydrogels for the Id1-siRNA targeting and its delivery and sustained release for the treatment of gastric cancer. To improve the siRNA delivery by stimulating the target of Id1-siRNA into the defect cells and prolonging the silencing effect, cationic PEI was further engaged for scaffold modification.…”
Section: Drug and Molecule Deliverymentioning
confidence: 99%
“…Collagen is another biologically compatible and safe natural polymer and is a suitable carrier for drug delivery. In a study performed by Peng et al, localized and sustained release of siRNA-loaded collagen formulations were prepared for use in vivo gastric cancer, and positive results were obtained [57].…”
Section: Natural Polymersmentioning
confidence: 99%
“…[8,29] Scaffold-mediated RNA interference has been carried out through the surface immobilization or direct bulk encapsulation of siRNA in hydrogels, [30] nanofibers, [11] and sponge-based constructs. [8,29] Scaffold-mediated RNA interference has been carried out through the surface immobilization or direct bulk encapsulation of siRNA in hydrogels, [30] nanofibers, [11] and sponge-based constructs.…”
Section: Wwwadvancedsciencecommentioning
confidence: 99%